Construction and operation of a modular didactic unit for Proportional-Integral-Derivative (PID) level control in tank - Felipe Santos Pulcherio; Ana Clara Alves Justi; Júlio Cesar de Carvalho Miranda (The Journal of Engineering and Exact Sciences)
The construction and operation of a modular didactic unit for PID level control was carried out with the function of qualifying the student regarding the use of the instruments involved. The developed algorithm operated in Arduino together with a supplement, elaborating graphic visuals in real-time execution. It is expected that the use of this unit will enable the technical qualification, applied to problem resolution and implementation of solutions, according to teachings in class.